Optical and thermal responses of silicene in Xene heterostructures. Issue 8 (5th July 2022) - Bonaventura, Eleonora; Dhungana, Daya S.; Martella, Christian; Grazianetti, Carlo; Macis, Salvatore; Lupi, Stefano; Bonera, Emiliano; Molle, Alessandro
Abstract : Buffering silicene with a stanene interlayer proves to be effective in breaking its strong interaction with the supporting Ag(111) substrate. Unprecedented optothermal response of silicene discloses new applications in thermoelectrics and plasmonics. Abstract : Stabilization of silicene and preservation of its structural and electronic properties are essential for its processing and future integration into devices. The stacking of silicene on stanene, creating a Xene-based heterostructure, proves to be a viable new route in this respect. Here we demonstrate the effectiveness of a stanene layer in breaking the strong interaction between silicene and the Ag(111) substrate. The role of stanene as a 'buffer' layer is investigated by analyzing the optical response of epitaxial silicene through both power-dependent Raman spectroscopy and reflectivity measurements in the near infrared (NIR)–ultraviolet (UV) spectral range. Finally, we point out a Xene-induced shift of the silver plasma edge that paves the way for the development of a new approach to engineering the metal plasmonic response.